Factors that influence the impact of internet on selected sectors in Iloilo City - Caldeo, Richelyn P.; Denila, Horylen D.; Escaner, Hilzeber A.; Lutero, Dawn C.; Manzanida, Ma. Louie L.; Seneres, Dhonabee B. (1998.)
Executive summary-The primary objective of the study was to evaluate the factors which influence the impact of Internet on educational, business and govenrment sectors. In attaining the objective, the researchers employed varied sampling and data gathering techniques, and subjkected the data to statistical analysis to detemrine their interrelationship and respective contribution to the impact of internet. The study revealed that individuals in the educational, business and government sectors are moderately familiar with Internet. Specifically, business sector is likely to be very familiar with Internet, educational sector is moderately adept with Internet while the government sector has the least knowledge. In terms of organizational position, top management is moderately to very familiar with Internet, middle management is least to moderately familiar, supervisory management is moderately to very familiar, and line and staff is not familiar to moderately familiar with Internet. Age, civil status, and annual family income are negligibly familiar with Internet while sex is directly and substantially correlated. Stated conversely, Internet familiarity depends on sex, accessibility, its positive and negative effects, organizational position and sectoral classification. As to accessibility, among those who are able to access the Internet, 30.83% belong to the business sector, 27.52% are students and 24.06% belong to the government sector. Knowledge, friends, time, income and job or work were factors identified to contribute to gaining access to Internet. age, annual family income, civil status and sex are positively and negligibly correlated to te ability to operate. Accessiibility however, is not dependent upon the individual's sectoral classification. The impact of Internet is dependent on the individual's familiarity with and accessibility to Internet.
Research Paper (BA 200-Business Research). -- Iloilo City : University of the Philippines in the Visayas - College of Management, March 23, 1998.